FRAGMENTASI OTORITAS KEAGAMAAN DI MEDIA SOSIAL: ANALISIS TAFSIR TEMATIK - Avuani Alrijal Choir Umam; Muhammad Alif (Adisam Publisher, 2026)
This research seeks to examine the issue of the division of religious authority on social media through the lens of the Qur’an utilizing a thematic exegesis (maudhū‘i) method. The quick evolution of social media has greatly changed how religious information is shared, with authority shifting away from conventional scholars or religious organizations to individuals who actively spread religious messages online. This change has resulted in the appearance of various sources of religious guidance, possibly creating variations in interpretation within the community. This study uses a qualitative approach rooted in library research, applying a thematic exegesis method to gather and examine Qur’anic verses concerning religious authority, knowledge, and the moral duty in delivering religious teachings. The data undergo a descriptive-analytical analysis to uncover the Qur’anic notion of religious authority and its significance in relation to modern challenges. The results indicate that the Qur’an prioritizes the significance of religious authority based on genuine knowledge, ethical integrity, and accountability in sharing truth, while also forbidding the spread of religious teachings without credible knowledge. The division of religious authority on social media presents both advantages and obstacles: it allows wider access to religious information, but it also poses the danger of confusion and misunderstanding because of the lack of definitive standards of authority. Consequently, a discerning and careful approach to religious information, coupled with the enhancement of religious literacy, is vital for preserving the integrity of religious authority in the digital age.